USE OF INFORMATION TECHNOLOGY IN RESEARCH WORK OF FUTURE SOFTWARE ENGINEERS - Vinnik, М.О. (Journal of Information Technologies in Education (ITE), 2015)
The article describes practical cooperation experience of Kherson State University’s lecturers group and students on software creation for automation, selection and processing of information about the universities scientists publication on the Internet. Recently, much attention is paid to scientometric bases by scientific societies of Eastern Europe. Large number of countries creates their own scientometric bases, platforms and other services. Working on familiar projects the future software engineers can be ready to implement similar tasks as for own country and for the world leaders. The result of research group work should be creation of software tools to support the business processes of research activities at the university. The involvement of students in research work allows using their creativity and employment potential for solving urgent problems of university, raising research competence of students’ professional skills in computer science and software engineering, which are involved in design and development of real software product. Participation of students in each stage is essential element of research group work. While creating software, students receive not only theoretical and practical knowledge of research work but also enhance their professional competences, as projects implementation is the closest to the professional software engineer’s work.